Bringing agency back into the study of partisan politics: a note on recent developments in the literature on party politics - Wenzelburger, Georg; Zohlnhöfer, Reimut (Sage Publ., 2021)
The question of whether political parties make a systematic difference in terms of public policies is one of the classics of comparative public policy research. However, unstable class cleavages and changing party strategies challenge the assumptions of traditional partisan theory, namely that parties represent a stable group of voters and implement policies according to the preferences of this group. Against this backdrop, several recent studies have called for an “electoral turn” in partisan theory and suggest establishing a party–voter link on the microlevel, depending on the policy area at stake. In this article, we propose a different view on partisan effects. While we do not argue that public opinion is unimportant for parties, we maintain that the electoral turn literature has a tendency to black-box the political actors and their preferences, because they become mere agents of voter preferences. Our argument builds on a growing literature that shows that political actors both at the party member and the elite level do have preferences and that these may ormay not be congruent with those of the voters. Hence, the effect of partisan ideology on public policies may also be situated on the level of the parties or policy-makers themselves.
In: Party Politics, 27 (2021), Nr. 5. pp. 1055-1065. ISSN 1354-0688 (Print-Ausg.), 1460-3683 (Online-Ausg.)